Dynamic Expression of m6A Regulators During Multiple Human Tissue Development and Cancers - Zhang, Ya; Xu, Sicong; Xu, Gang; Gao, Yueying; Li, Si; Zhang, Ke; Tian, Zhanyu; Guo, Jing; Li, Xia; Xu, Juan; Li, Yongsheng (Frontiers in Cell and Developmental Biology, 2021)
N6-methyladenosine (m6A) plays critical roles in human development and cancer progression. However, our knowledge regarding the dynamic expression of m6A regulators during human tissue development is still lacking. Here, we comprehensively analyzed the dynamic expression alterations of m6A regulators during seven tissue development and eight cancer types. We found that m6A regulators globally exhibited decreased expression during development. In addition, IGF2BP1/2/3 (insulinlike growth factor 2 MRNA-binding protein 1/2/3) exhibited reverse expression pattern in cancer progression, suggesting an oncofetal reprogramming in cancer. The expressions of IGF2BP1/2/3 were regulated by genome alterations, particularly copy number amplification in cancer. Clinical association analysis revealed that higher expressions of IGF2BP1/2/3 were associated with worse survival of cancer patients. Finally, we found that genes significantly correlated with IGF2BP1/2/3 were significantly enriched in cancer hallmark-related pathways. In summary, dynamic expression analysis will guide both mechanistic and therapeutic roles of m6A regulators during tissue development and cancer progression.